Smart Antenna Potential on Performance Improvement for Mobile Communication Systems - Ismail M. Jabber; Ansam M. Abed (Journal of Madenat Alelem University College, 2015)
Smart antennas have numerous important benefits in mobile communication systems. Smart antennas can provide higher system capacities by directing narrow beams toward the users of interest, while nulling other users not of interest. This allows for higher signal-to-interference ratios, lower power levels, and permits greater frequency reuse within the same cell. This, in turn, increases the system capacity and the quality of services. In this paper we analyze the effect of base-station sensitivity obtained by using smart antenna to increase capacity and reduced the mobile transmit power at different loads scenarios.